Assessment of fluoride intake from drinking water and toothpaste in 3-year-olds: preliminary results in Belgrade, Republic of Serbia - Djukić-Ćosić, Danijela; Antonijević, Evica; Mandinić, Zoran; Ćurčić, Marijana; Ćupić Miladinović, Dejana; Antonijević, Biljana; Matović, Vesna (Vojnosanitetski pregled, 2021)
Background/Aim. Fluoride has beneficial effect on dental caries prevention and enables high hardness of enamel. However, fluoride intake above optimal levels can have adverse effects on teeth and bones, especially in young children during the period of intense growth and teeth development. The aim of this study was to assess fluoride intake from water and toothpaste among 3-year-old children in Belgrade, Serbia, in the municipalities of Vračar and Novi Beograd. Methods. A questionnaire for the parents (n = 40) was used to provide information on the water consumption (tap and/or bottled water) and the brand of toothpaste used by children as well as the frequency of tooth brushing and the amount of toothpaste during brushing. Fluoride concentrations in water and toothpaste samples were determined electrochemically by using fluoride-selective electrode. Fluoride intake was estimated through a mathematical model commonly used by the U.S. Environmental Protection Agency. Results. The obtained results indicate no significant difference in daily fluoride intake through drinking water and toothpaste in 3-year-old children in Vračar (n = 19) compared to Novi Beograd (n = 21) (p > 0.05). However, all estimated fluoride levels (0.089–0.625 mg/day) are significantly lower than the optimal daily intake level for caries protection (0.7 mg/day for children up to 4 years, FNB-USA National Institute of Medicine) and two to six times lower than tolerable upper fluoride level for the children of same age (1.3 mg/day, FNB-USA National Institute of Medicine). Furthermore, calculated daily fluoride intake per kilogram body weight confirm very low fluoride intake by water and toothpaste in children of investigated municipalities in Belgrade, being significantly below the recommended an adequate intake (0.05 mg/kg/day, EFSA). Conclusion. This preliminary study has shown that daily fluoride intake in 3-year-olds is lower than tolerable upper fluoride level, even not sufficient for the prevention of dental caries.
Keywords: flouorides; child, preschool; drinking water; toothpastes; tooth diseases; surveys and questionnaires.